LEGAL STATE OF DOCTORS WITHOUT BORDERS (MÉDECINS SANS FRONTIÈRES) IN THE INTERNATIONAL LAW - Nooshin Bagherani; Abdolkarim Shaheydar; Bruce R. Smoller; Hossein Ale Kajbaf (Lampung Journal of International Law, 2022)
Médecins Sans Frontières (MSF) is a non-profit organization that offers health and medical services to people based on their requirements irrespective of race, gender, beliefs, religion, and political origins. Physicians, as the MSF's most important members, assist people in their greatest need. They provide services ranging from consultations, vaccinations, and primary care to the most complex surgeries. Given that the doctors in the organization are very active members of the MSF and understand the risk of their presence in dangerous regions with prevalent epidemic and contagious diseases or under distress, insecurity, and war in underdeveloped or third world countries, research into the legal status of this self-giving and venture group of the international society is critical. The legal status of humanitarian aid workers such as the physicians in doctors without borders in international law has not been studied and recognized. This is due to the absence of a complete definition of “humanitarian aid workers” in international humanitarian law. Furthermore, the issue of the status of humanitarian NGOs in international law is novel. Therefore, studying the legal status of the humanitarian aid workers is an essential case because they are exposed to many potential risks in facing armed conflicts. This research planned a web-based survey as part of our study to find articles, books, reports, or studies in relationship with national and international humanitarian organizations and workers, NGOs, and the legal status of these organizations and their workers. We did normative legal research using secondary data from the internet, references, etc. While the operation of the MSF is mainly aimed at supporting the survival and recovery of people within a war or disease outbreak-afflicted country, its efforts put the lives of its personnel at risk. Herein, we will investigate how the MSF can adequately support its primary staff, the physicians. We can get the response to this question by studying the legal status of the doctors without borders in international law.